The Influence of Digital Literacy on Social Media Capability and Competitive Advantage and Its Impact on Firm Performance - Stefen Oktafian; Mohammad Iqbal; Agung Nugroho L.I.F (Accounting Department,, 2025)
Purpose - This study aims to analyze the relationships among key variables in the digital business context, focusing on the impact of Digital Literacy (DL) on Firm Performance (FP), Social Media Capability (SMC), and Competitive Advantage (CA). It further examines how SMC influences both CA and FP, as well as CA's role in enhancing FP. By understanding these interconnections, this study provides strategic insights that help businesses leverage digital technology to improve competitiveness and performance. Design/methodology/approach - The study employs a quantitative approach, using survey data collected from 200 SME across various sectors in Malang. Structural Equation Modeling (SEM) was applied to test the proposed hypotheses. Findings: DL has a positive and significant effect on FP and SMC but does not significantly affect CA. SMC, however, has a strong positive impact on both CA and FP. Furthermore, CA significantly enhances FP, affirming its role as a key driver of business success. Practical implications - Practical implications include the need for SME to enhance digital literacy and social media capabilities to improve their competitive positioning and performance. Originality/value - The study's originality lies in its integration of DL, SMC, CA, and FP within the SME context in Malang City, offering novel insights into how digital transformation drives business outcomes. Paper type - Explanatory Research